Instructional Methods in Speaking Classes: Reviewing Literature - Veni Nella Syahputri; Nyak Mutia Ismail (Universitas Serambi Mekkah, 2022)
This review article presents varied perspectives on teaching methods used in speaking classes. The aims of this study is to give insights on teaching methods that can be adopted, combined, or adapted in accordance with the actual condition of the classes. This information is considered to be important for English teachers, specifically, and for all language instructors and researchers, in general. There are 12 research articles being reviewed in this article under the topic of teaching methods in speaking. These articles were summarized to see the essentials being delivered, challenges presented, and further queries left unanswered which are beneficial for further research to be explored. The result shows that the most striking element in speaking classes is verbal oral expression. All teachers must encourage their students to speak. Later, it is psychological aspects (moods) and learning environment. Mostly, happy environment—not stiff and meticulous environment—brings more willingness for students to speak. Last, not giving them pressure on grammatical aspects is also a spur towards their motivation to speak. Keywords: Teaching Speaking, Learning Speaking, ELT Methods, and EFL Methods